EMBEDDED MICROCONTROLLER BASED REAL TIME SUPPORT FOR DISABLED PEOPLE USING GPS (International Journal of Engineering Sciences & Management Research, 2016)
This paper contains prototype system which comes to handy for the blind .the prototype system is based on the microcontroller and GPS receiver module with the usage of which the blind person will be able to be guided to the preloaded locations. There will be a proxy sensor through which the person will be alerted by the voice module if he comes across an obstacle. Here we are using the RF camera through which the video can be received by the RF receiver and can have a visual of the surroundings of the blind person. Here we are using the GSM modem so that the prototype system carried by the person will send the message to the already loaded mobile numbers which might belongs to the relations of the blind person